2020
DOI: 10.1111/sode.12447
|View full text |Cite
|
Sign up to set email alerts
|

The classroom relational environment and children’s early development in preschool

Abstract: Prior research on the quality of teacher-child interactions generally has examined the average child experience in the preschool classroom and documented modest associations with children's early learning and development (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 79 publications
(126 reference statements)
2
24
0
1
Order By: Relevance
“…Although classroom-level and dyadic teacher-student relationships are related (Buyse et al, 2008;Moen et al, 2019;Walker and Graham, 2019), the impact of dyadic teacher-student relationships on student development can be distinguished from the impact of relationships at the classroom level (Buyse et al, 2009;Rucinski et al, 2018;Nguyen et al, 2020). A low-quality dyadic teacher-student relationship can subvert the benefits of high-quality classroom environments (Crosnoe et al, 2010;Nguyen et al, 2020) and classroom-level emotional support cannot compensate for lowquality dyadic relationships (Rucinski et al, 2018). These results highlight the importance of teachers' competence to build positive relationships with each of their students.…”
Section: Affective Teacher-student Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although classroom-level and dyadic teacher-student relationships are related (Buyse et al, 2008;Moen et al, 2019;Walker and Graham, 2019), the impact of dyadic teacher-student relationships on student development can be distinguished from the impact of relationships at the classroom level (Buyse et al, 2009;Rucinski et al, 2018;Nguyen et al, 2020). A low-quality dyadic teacher-student relationship can subvert the benefits of high-quality classroom environments (Crosnoe et al, 2010;Nguyen et al, 2020) and classroom-level emotional support cannot compensate for lowquality dyadic relationships (Rucinski et al, 2018). These results highlight the importance of teachers' competence to build positive relationships with each of their students.…”
Section: Affective Teacher-student Relationshipsmentioning
confidence: 99%
“…The importance of the affective qualities of dyadic teacherstudent relationships, both for child development and teacher well-being, has repeatedly been demonstrated (e.g., McGrath and Van Bergen, 2015;Corbin et al, 2019). Students who have a close relationship with their teacher for instance hold more positive attitudes toward school, achieve better in class, and are more likely to develop positive peer relations (Roorda et al, 2017(Roorda et al, , 2020Ansari et al, 2020a), while students who have a conflictual relationship with their teacher are at risk for negative outcomes and the amplification of initial internalizing and externalizing problems (Roorda et al, 2014;Ansari et al, 2020a;Nguyen et al, 2020;Roorda and Koomen, 2021). Likewise, close teacher-student relationships contribute to teachers' self-efficacy, sense of personal accomplishment, job satisfaction, and professional motivation (Hagenauer et al, 2015;Corbin et al, 2019;Evans et al, 2019;Aboagye et al, 2020), whereas conflictual relationships are an important source of teacher stress and are predictive of burnout symptoms such as emotional exhaustion (Milatz et al, 2015;Corbin et al, 2019;Ansari et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Children with high quality relationships with teachers are more engaged, more task‐oriented and generally perform better at school. Also children have been found to benefit only from high‐quality classroom instruction when they have a high‐quality dyadic relationship with the teacher (Nguyen et al., 2020). The effects of dyadic teacher–child relationships (TCRs) are not limited to adjustment and achievement at school, but extend beyond the classroom to children’s psychosocial functioning and mental health.…”
Section: Introductionmentioning
confidence: 99%
“…From the available literature, some studies focus on teachers' interactions with individual students instead of the wholeclassroom relationships (Roorda D. L. et al, 2013;Williford et al, 2017;Lippard et al, 2018;Koenen et al, 2019;Nguyen et al, 2020;de Ruiter et al, 2021;Koenen et al, 2022). According to Pianta et al (2003), teacher-student relationships are dyadic microsystems in which teachers' and students' personal and behavioral characteristics influence how they perceive their relationship and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…The reciprocal exchanges during oneon-one interactions between teachers and students contribute to each individual's cognitive model or representations of their relationship and develop their expectations that guide subsequent interactions, behaviors and perceptions in the whole-classroom level (Pianta, 1999). Recently, Nguyen et al (2020) explored whether teacher-student interactional quality at the classroom level and the dyad level influence the students' outcomes. Results showed that when students experience a positive teacher-child dyadic relationship they display increased engagement in school activities and improved academic achievement.…”
Section: Introductionmentioning
confidence: 99%